Review on distribution, culture practices, food and feeding, brood development and artificial breeding of Seabass, Lates calcarifer (BLOCH 1790): Bangladesh perspective - Haque, Mohammed Ashraful; Hossain, Md Istiaque; Uddin, Sheikh Aftab; Dey, Probin Kumar (Research in Agriculture Livestock and Fisheries, 2020)
Seabass, Lates calcarifer (Bloch 1790) is an euryhaline and a popular fish in south and southeast Asian countries due to its higher growth rate, giant size, excellent taste and higher market demand. It is locally known as Bhetki or Koral and available around the year in the estuarine and coastal regions of Bangladesh. In many countries (e.g. Australia, India, Malaysia, Philippines, Thailand etc.), the species is artificially propagated and commercially cultured. The breeding technology has not yet been developed in Bangladesh. Now a days Bangladesh is progressing day by day in freshwater aquaculture but it is far behind in case of coastal and mariculture. To get the mass seed production of fry/fingerlings of seabass, we need to develop the artificial breeding technology of the said species. There are only a few studies published on biology, aquaculture, brood development and artificial breeding activities of seabass in Bangladesh where investigators used live feed (Tilapia) and small indigenous fish species (SIFS) on brood development in captivity but none could adapt to formulated feed on seabass aquaculture. Some researchers made attempt to develop seabass broodstock for artificial breeding purpose, but none can success in captive condition in Bangladesh. Only one breeding trial conducted by stripping method using wild brood, but the development of the fertilized eggs ceased attaining up to the neurola stage, Res. Agric., Livest. Fish.6(3): 405-414, December 2019